ARQA-BATÍS ÓZBEKSTAN AYMAǴÍNDAǴÍ HAYWANLAR ShISTOSOMOZÍ EPIZOOTOLOGIYASÍNÍŃ ÓZGEShELIKLERI - Ubbiniyazova, J.K. (SCIENCE and SOCIETY, 2025)
The article presents the results of parasitological studies of domestic and wild mammals and their infection with the Schistosoma turkestanicum Sbrjabin, 1913 trematode in the conditions of the northwestern region of Uzbekistan. Infection in the examined animals was cattle - 88.0%, sheep - 54.2%, goats - 28.8%. The intensity of animal infection ranged from ten to several thousand specimens.